Testing Architectures for Real Time Systems - Alves, Everton L. G.; Machado, Patricia D. L.; Ramalho, Franklin (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
Test automation is a challenging activity. The design of test architectures for enabling the automatic execution of test cases is a hard task to be executed. For Real-Time Systems (RTS) the difficulties of developing good test architecture are increased because of their inherent characteristics (e.g. concurrence, timing constraints and reactivity). To support the test architecture design, the OMG proposed the UML Testing Profile (UTP) which allows the Model-Driven Testing (MDT) application. In the RTS context, MDT may enable the composition and automatic generation of test architectures at different abstraction levels. However, UTP does not offers specific mechanisms to support the specification of test architectures for RTS. This work proposes: i) an UTP extension (UTP RT) for support the specification of RT test architectures, and ii) a tool (RTTAG) that automatically generates test architectures, based on UTP RT profile, at the independent and dependent platform level. Case studies were executed shown the applicability and completeness of the profile and tool developed.